2018
DOI: 10.1259/bjrcr.20170109
|View full text |Cite
|
Sign up to set email alerts
|

Update on a rare mandibular osteolytic lesion in childhood: the buccal bifurcation cyst

Abstract: Buccal bifurcation cyst is a rare, uncommon buccal cystic lesion associated with the permanent mandibular first molar in children just prior to tooth eruption, and is categorized by the World Health Organization as an odontogenic cyst occurring in a vital tooth, near the buccal cervical margin of the lateral aspect of a root, as a result of an inflammatory process in a periodontal pocket. The aim of this study is to present a series of three similar mandibular buccal bifurcation cyst cases, by providing clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The pathogenesis of inflammatory collateral cysts is postulated to be a combination of the accumulation of microbial plaque and a break in oral mucosa during tooth eruption. This initiates the release of inflammatory mediators and the formation of non-keratinised, hyperplastic stratified squamous cystic lining with inflammatory infiltration on the lateral root surface (De Grauwe et al 2018;Maruyama et al 2015;Philipsen et al 2004). Factors that predispose to plaque accumulation such as enamel pearls at the bifurcation are likely to be contributing factors.…”
Section: Inflammatory Collateral Cystmentioning
confidence: 99%
“…The pathogenesis of inflammatory collateral cysts is postulated to be a combination of the accumulation of microbial plaque and a break in oral mucosa during tooth eruption. This initiates the release of inflammatory mediators and the formation of non-keratinised, hyperplastic stratified squamous cystic lining with inflammatory infiltration on the lateral root surface (De Grauwe et al 2018;Maruyama et al 2015;Philipsen et al 2004). Factors that predispose to plaque accumulation such as enamel pearls at the bifurcation are likely to be contributing factors.…”
Section: Inflammatory Collateral Cystmentioning
confidence: 99%
“…Buccal bifurcation cyst (BBC) is an unusual inflammatory odontogenic cyst that occurs at the buccal region of the permanent mandibular first or second molars in children aged 6-8 years old [1,2]. Some authors reported that it is most common in 6-to 15-year-old patients and it is not found in adults [3,4]. BBC does not occur in the maxilla and can be bilateral [3].…”
Section: Introductionmentioning
confidence: 99%
“…The BBC diagnosis is primarily based on specific clinical and radiographic findings and it cannot be dignosed from the histopathologic features [1]. CBCT characteristics include buccal expansion, sometimes interradicular bone loss, periosteal bone reaction and resorption of the vestibular plate [4]. The treatment of choice is enucleation and curettage of the lesion without extraction of the vital involved tooth.…”
Section: Introductionmentioning
confidence: 99%